PEMBELAJARAN TWO STAY TWO STRAY DAN SNOWBALL THROWING TERHADAP KEMAMPUAN BERFIKIR KRITIS - Apriliani Rahmawati; Pargito Pargito; Darsono Darsono (Faculty of Teacher Training and Education, University of Lampung, 2013)
This study aims to analyze differences of students critical thinking skills in social studies (Two Stay Two Stray and Snowball Throwing). The method used is the quasi-experimental design to provide treatment to different classes. The result showed that there are differences of students’ critical thinking skills in social studies (Two Stay two Stray and Snowball Throwing) learning models and initial ability (high and low), there are differences in students’ critical thinking skills in social studies which the learning used Two Stay two Stray and Snowball Throwing without regarding to students initial ability, there are differences in students’ critical thingking skills that have high and low initial ability without considering the learning model, there is an interaction between the learning with initial ability of the students critical thinking skills.Penelitian ini bertujuan untuk menganalisis perbedaan kemampuan berfikir kritis siswa pada mata pelajaran IPS antarmodel pembelajaran (Two Stay Two Stray dan Snowball Throwing). Metode yang digunakan yaitu menggunakan rancangan eksperimen semu dengan memberikan perlakuan pada dua kelas yang berbeda. Hasil penelitian menunjukkan bahwa ada perbedaan kemampuan berfikir kritis siswa pada mata pelajaran IPS antarmodel pembelajaran (Two Stay Two Stray dan Snowball Throwing) dan antar kemampuan awal (tinggi dan rendah), ada perbedaan kemampuan berfikir kritis siswa pada mata pelajaran IPS yang pembelajarannya menggunakan pembelajaran Two Stay Two Stray dan Snowball Throwing tanpa memperhatikan kemampuan awal siswa, ada perbedaan kemampuan berfikir kritis pada mata pelajaran IPS yang memiliki kemampuan awal tinggi dan rendah tanpa mempertimbangkan model pembelajaran, ada interaksi antara model pembelajaran dengan kemampuan awal terhadap kemampuan berfikir kritis.Kata kunci: kemampuan berfikir kritis, snowball throwing, two stay two stray